Analysis of Heavy Equipment Productivity in Road Rehabilitation Projects on Nanga Semangut-Putussibau-Tanjung Kerja and Putussibau-Nanga Era Roads - Paskasio, Jhoni; Nuh, Safaruddin M.; Rafie, Rafie (Fakultas Teknik Universitas Tanjungpura, 2024)
This study analyzes the productivity of heavy equipment in road rehabilitation projects for the Nanga Semangut-Putussibau-Tanjung Kerja and Putussibau-Nanga Era routes to evaluate efficiency and operational costs. The research compares various equipment types' productivity and working hours across two time segments. The findings reveal that dump trucks demonstrated high productivity with shorter working durations in Time Segment 1, while asphalt finishers, pneumatic tire rollers, and tandem rollers maintained stable productivity with varying hours. Segment 1 was more efficient, exhibiting higher productivity and lower rental costs than Segment 2, which showed longer operational hours and increased total costs. The study also assessed heavy equipment combinations, identifying Combination 3, featuring 18 dump trucks with an 8 m ³ capacity, as the most efficient. This combination achieved the shortest completion time of 44 days with a total cost of IDR 2,255,104,022.93. These results highlight the importance of optimal equipment selection, strategic resource allocation, and cost management in ensuring successful road rehabilitation projects.